2008
DOI: 10.1590/s0074-02762008000600013
|View full text |Cite
|
Sign up to set email alerts
|

Association of the presence of residual anti-Toxoplasma gondii IgM in pregnant women and their respective family groups in Miracema, Northwest Rio de Janeiro, Brazil

Abstract: The seroprevalence of toxoplasmosis in 832 pregnant women in Miracema, Rio de Janeiro, was determined and 75.1% (625) The parasite Toxoplasma gondii is one of the most frequent to infect human beings and is found in almost one-third of the world population (Dubey 2004). Patients are frequently asymptomatic and toxoplasmosis has no relevant repercussions on the patient. However, infected fetuses and immunodeficient individuals may present with serious or even fatal clinical outcomes (Gross 1996, Vidigal et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
3
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
6
3
1
Order By: Relevance
“…In a study done in India, it was found to be 13.1%. Lower seroprevalance were found in studies done in other countries (Ribeiro et al 2008, Alvarado-Esquivel et al 2009. Among the women with BOH, prevalence of IgM antibodies against T. gondii was found to be 17.84% which was in concordance with the finding of a comparable study (15.43%) conducted earlier (Lamichhane et al 2007).…”
Section: Resultssupporting
confidence: 86%
“…In a study done in India, it was found to be 13.1%. Lower seroprevalance were found in studies done in other countries (Ribeiro et al 2008, Alvarado-Esquivel et al 2009. Among the women with BOH, prevalence of IgM antibodies against T. gondii was found to be 17.84% which was in concordance with the finding of a comparable study (15.43%) conducted earlier (Lamichhane et al 2007).…”
Section: Resultssupporting
confidence: 86%
“…Higher prevalence than that found in this paper was observed in Vitória (ES) (Areal and Miranda, 2008), Porto Alegre (RS) (Spalding et al, 2005), Recife (PE) (Porto et al, 2008) and Miracema (RJ) (Ribeiro et al, 2008), with serological prevalence of 73.5%, 74.5%, 74.7%, and 75.1%, respectively.…”
Section: Discussioncontrasting
confidence: 66%
“…In this paper, the prevalence for IgM anti-T. gondii antibodies was 1.0%, a lower result than that found in researches conducted in Palotina (PR) (Bittencourt et al, 2012), Vitória (ES) (Areal and Miranda, 2008), Londrina (PR) (Mandai et al, 2007), Rolândia (PR) (Dias et al, 2011), Miracema (RJ) (Ribeiro et al, 2008) and Recife (PE) (Porto et al, 2008), which detected 1.1%, 1.3%, 1.7%, 1.9%, 2.0%, and 2.8%, respectively. In the state of Santa Catarina (Sandrin et al, 2012), researchers have found a prevalence of 0.57%.…”
Section: Discussioncontrasting
confidence: 64%
“…The median of IgG Toxoplasma prevalence was 38.5% [64] for Bangladesh. IgG high rate of detection was reported for Brazil [50] (75%, 832 pregnant women), while the lowest rate was for Thailand [38] (5.3%, 831 pregnant women). IgM lowest rate reported for China [49] (0%, 235 pregnant women) and Vietnam [59] (0%, 300 pregnant women), while the highest rate reported for Ghana [87] (76.1%, 159 pregnant women).…”
mentioning
confidence: 99%